2009
DOI: 10.1111/j.1872-034x.2009.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose erythropoietin‐beta improves anemia and maintains ribavirin dose in chronic hepatitis C patients receiving combination therapy with ribavirin plus pegylated interferon Alfa‐2b

Abstract: Low-dose EPO-beta can maintain RBV dose and increase Hb levels in anemic chronic HCV patients receiving combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The current data showed that HCV genotype 1 patients who failed a prior standard of care had a lower chance of achieving SVR [90][91][92], giving new antiviral therapies more important role for patients. In conclusion, most of the new drugs described above need the combination of peg-IFN and RBV at the same time to allow them to work in an anti-HCV manner.…”
Section: Vitamin Dmentioning
confidence: 86%
“…The current data showed that HCV genotype 1 patients who failed a prior standard of care had a lower chance of achieving SVR [90][91][92], giving new antiviral therapies more important role for patients. In conclusion, most of the new drugs described above need the combination of peg-IFN and RBV at the same time to allow them to work in an anti-HCV manner.…”
Section: Vitamin Dmentioning
confidence: 86%
“…Erythropoietic growth factor, erythropoietin, is widely used in the USA and some Western countries to increase hemoglobin level, maintain the doses of RBV and improve treatment compliance. [11][12][13][14][15][16][17][18][19][20][21] However, the adjuvant use of erythropoietin in the setting of anti-HCV therapy has not been approved in Japan. 22 In addition, the impact of erythropoietin administration on SVR remains unclear.…”
Section: H Epatitis C Virus (Hcv) Infection Remains Anmentioning
confidence: 99%
“…To overcome this obstacle, several groups reported employment of human recombinant erythropoietin (EPO) administration to alleviate anemia and thereby complete the therapy without RBV reduction in patients under IFN/RBV or PEG IFN/RBV combination therapy. [3][4][5][6][7][8] Most of the reports describe the successful role of EPO as an alternative to RBV dose reduction, and meta-analysis demonstrates that EPO administration can considerably enhance SVR with no adverse event due to EPO. 9 In triple therapy, anemia develops more frequently than in PEG IFN/RBV combination therapy, consequently resulting in poor adherence to RBV.…”
Section: Introductionmentioning
confidence: 99%